Properties of neural crest-like cells differentiated from human embryonic stem cells - Křivánek, J; Švandová, E; Králik, J; Hajda, Š; Fedr, R; Vinarský, V; Jaroš, J; Souček, K; Buchtová, M; Matalová, E; Hampl, A (Folia biologica, 2014)
Neural crest cells (NCCs) derive early in vertebrate ontogenesis from neural tube as a population of migratory cells with exquisite differentiation potential. Abnormalities in NCC behaviour are cause of debilitating diseases including cancers and a spectrum of neurocristopathies. Thanks to their multilineage differentiation capacity NCCs offer a cell source for regenerative medicine. Both these aspects make NCC biology an important issue to study, which can currently be addressed using methodologies based on pluripotent stem cells. Here we contributed to understanding the biology of human NCCs by refining the protocol for differentiation/propagation of NCClike cells from human embryonic stem cells and by characterizing the molecular and functional phenotype of such cells. Most importantly, we improved formulation of media for NCC culture, we found that poly-L-ornithine combined with fibronectin provide good support for NCC growth, we unravelled the tendency of cultured NCCs to maintain heterogeneity of CD271 expression, and we showed that NCCs derived here possess the capacity to react to BMP4 signals by dramatically up-regulating MSX1, which is linked to odontogenesis.
Keywords: buněčná diferenciace; MSX1 Transcription Factor; Humans; Naphthalenes; transkripční faktor MSX1; embryonální kmenové buňky; Neural Crest; naftaleny; Phenotype; Embryonic Stem Cells; lidé; Biomarkers; Bone Morphogenetic Protein 4; kostní morfogenetický protein 4; biologické markery; Adapalene; Flow Cytometry; fenotyp; Cell Differentiation; polymerázová řetězová reakce; Polymerase Chain Reaction; průtoková cytometrie; adapalen; crista neuralis